How to solve 8(x+1/x)^2+4(x^2+1/x^2)^2-4(x^2+1/x^2)(x+1/x)^2=(x+4)^2 ?

Hello friends,
Welcome to my article 8(x+1/x)^2+4(x^2+1/x^2)^2-4(x^2+1/x^2)(x+1/x)^2=(x+4)^2 .
This article is taken from the simplification lesson, in this article we have been told how to solve the problem easily by doing addition, subtraction, multiplication, division and fractionation.or complete information on how to solve this 1/x+1+2/x+2=5/x+4, read and understand it carefully.

Let us read / understand about this article 8(x+1/x)^2+4(x^2+1/x^2)^2-4(x^2+1/x^2)(x+1/x)^2=(x+4)^2

First of all we should write the article on the page of the notebook.

8(x+1/x)^2+4(x^2+1/x^2)^2-4(x^2+1/x^2)(x+1/x)^2=(x+4)^2 ,

To solve this question write in this way,

\displaystyle 8{{\left( {x+\frac{1}{x}} \right)}^{2}}+4{{\left( {{{x}^{2}}+\frac{1}{{{{x}^{2}}}}} \right)}^{2}}-4\left( {{{x}^{2}}+\frac{1}{{{{x}^{2}}}}} \right).{{\left( {x+\frac{1}{x}} \right)}^{2}}={{(x+4)}^{2}}

\displaystyle 8\left( {{{x}^{2}}+\frac{1}{{{{x}^{2}}}}+2} \right)+4\left( {{{x}^{4}}+\frac{1}{{{{x}^{4}}}}+2} \right)-4\left( {{{x}^{2}}+\frac{1}{{{{x}^{2}}}}} \right).\left( {{{x}^{2}}+\frac{1}{{{{x}^{2}}}}+2} \right)={{(x+4)}^{2}}

\displaystyle 8\left( {{{x}^{2}}+\frac{1}{{{{x}^{2}}}}+2} \right)+4\left( {{{x}^{4}}+\frac{1}{{{{x}^{4}}}}+2} \right)-4\left[ {{{x}^{4}}+1+2{{x}^{2}}+1+\frac{1}{{{{x}^{4}}}}+\frac{2}{{{{x}^{2}}}}} \right]={{(x+4)}^{2}}

\displaystyle 8{{x}^{2}}+\frac{8}{{{{x}^{2}}}}+16+4{{x}^{4}}+\frac{4}{{{{x}^{4}}}}+8-4{{x}^{4}}-4-8{{x}^{2}}-4-\frac{4}{{{{x}^{4}}}}-\frac{8}{{{{x}^{2}}}}={{(x+4)}^{2}}

\displaystyle 8{{x}^{2}}-8{{x}^{2}}+\frac{8}{{{{x}^{2}}}}-\frac{8}{{{{x}^{2}}}}+4{{x}^{4}}-4{{x}^{4}}+\frac{4}{{{{x}^{4}}}}-\frac{4}{{{{x}^{4}}}}+8-4-4+16={{(x+4)}^{2}}

\displaystyle 8-8+16={{(x+4)}^{2}}

\displaystyle 16={{(x+4)}^{2}}

\displaystyle 16={{x}^{2}}+{{4}^{2}}+2.x.4

\displaystyle 16={{x}^{2}}+16+8x

\displaystyle 16-{{x}^{2}}-16-8x=0

\displaystyle -{{x}^{2}}-8x=0

\displaystyle -({{x}^{2}}+8x)=-(0)

\displaystyle {{x}^{2}}+8x=0

\displaystyle x(x+8)=0

\displaystyle x+8=0

\displaystyle x=-8Answer

The formula used in this question,

\displaystyle {{(a+b)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab


This article 8(x+1/x)^2+4(x^2+1/x^2)^2-4(x^2+1/x^2)(x+1/x)^2=(x+4)^2 , has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.
Your question will be answered from our side.

Thank you once again from our side for reading or understanding this article completely.

See also  How to solve is 1/2 bigger than 1/3 ?

1 thought on “How to solve 8(x+1/x)^2+4(x^2+1/x^2)^2-4(x^2+1/x^2)(x+1/x)^2=(x+4)^2 ?”

Leave a Comment